Development of an odorous repellent against common voles (Microtus arvalis) in laboratory screening and subsequent enclosure trials - Schlötelburg, Annika; Bellingrath-Kimura, Sonoko; Jacob, Jens (Journal of Pest Science, 2019)
Common voles (Microtus arvalis) can cause severe crop damage in European agriculture and are usually managed with rodenticides. Population dynamics and behavioral studies question rodenticide effectiveness, and an ecologically based management is needed. A useful addition to such a toolbox could be repelling odor barriers along field margins minimizing migration of voles to crops. We screened 17 plant products and mammalian scents in T-maze trials to test their repelling effects. The most repelling compounds (carrot seed oil (CS), black pepper oil (BP), spruce needle oil (SN), benzaldehyde (BA), BA and BP in double concentration (dc), combinations of BP + BA and BP + CS) were tested further in enclosures. We measured in four populations how often voles crossed enclosure compartments through channels treated with a compound or without a compound. In addition, the amount of rolled oats eaten by voles near treated and untreated channels was compared. In enclosures, voles avoided significantly channels treated with BP (79% more crossings through the control channel) and BP (dc) (42%). Voles consumed significantly more rolled oats near control channels than in the presence of BP + CS (72% more feeding at control), CS (51%), BA (dc) (36%), BP (32%) and BA + BP (28%). This demonstrated for the first time that natural compounds can reduce uptake of a highly attractive food source in common voles under semi-natural conditions. BP + CS was the most successful feeding deterrent and has the potential to be included in an ecologically based management approach.